Course grade calculation using fuzzy logic (CGCFL) - Nurhidayah, Muhamad Zahari (2011)
Grade Calculation using Fuzzy Logic System is a system that developed to calculate the final grade of Data Structure and Algorithms student's more accurate and valuable result. Nowadays,the calculation of student grade for data structure subject based on three categories which are cognitive, psychomotor and affective.However,in the current scenario, the final grade not considered at all on the categories. Example of the current situation is if the students get low mark in psychomotor, however the others categories student get excellent,the final result still show that the student pass the course.To produce high quality of graduate, these three categories must be considered.Because of this situation,this system had been developed by implement new concept using fuzzy logic and use Mamdani inferences to calculate the final grade student accurately.After done the development and implementation process, the result show that the system can produces almost 90% accurate value.This is because the new techniques of defuzzification had been implemented which are center of gravity (COG) and mean of maximum (MOM). However, the problem is there are some value that no really accurate. This happens because of more techniques need to be used. This system is better than manual system because it calculates all the value automatically and the three categories are being considered.